Strathcona example recommendation tool. - Holmes, Reid (Software engineering notes.)
Using the application programming interfaces (API) of large software systems requires developers to understand details about the interfaces that are often not explicitly defined. However, documentation about the API is often incomplete or out of date. Existing systems that make use of the API provide a form of implicit information on how to use that code. Manually searching through existing projects to find relevant source code is tedious and time consuming. We have created the Strathcona Example.Recommendation Tool to assist developers in finding relevant fragments of code, or examples, of an API's use. These examples can be used by developers to provide insight on how they are supposed to interact with the API.